Website-Based Contextual Learning Design of Han Script - Mulawarni Mulawarni; Emzir Emzir; Ratna Dewani (Universitas Sebelas Maret, 2020)
This study aims to produce a website-based contextual learning prototype design of han script used for training of Han script learning by using a contextual approach. Prototype Research on Contextual Learning Design of Han Script Based on Website is the answer to the problems faced by Mandarin Language teachers in SMA/SMK/MA in learning Han script. By using the ADDIE model focused on the Design step based on document analysis and literature review, the 30 Han characters chosen for daily use based on the formation of the word 造字方法